Nasal septal deviation and olfactory dysfunction: septoplasty and autoplatelet mesoconcentrate - Tsepkolenko, Oleksandra; Pukhlik, S.M. (Ukrainian Journal of Ophthalmology, 2023)
Background: Nasal septal deviation (NSD) prevalence rates in the general population range between 75% and 89.2%. The disease results in disorders of the ear, throat and nose, olfactory dysfunction (OD) in the form of hyposmia or anosmia, nasolacrimal duct obstruction, and, consequently, chronic dacryocystitis and low quality of life. Surgery for NSD (septoplasty) can be followed by postoperative anosmia. The three-year COVID-19 pandemic worsened the histories of candidates for septoplasty and the prognosis for surgical outcome in terms of restoration of smell. The methods available for the treatment of OD require close cooperation of specialties like ophthalmology, otorhinolaryngology and neuropathology. Cell-therapy technologies and application of platelet-reach plasma (PRP) seem to be promising in the treatment of NSD and OD. Purpose: To improve the efficacy of septoplasty for patients with NSD-associated OD through the use of autoplatelet mesoconcentrate (APMC). Material and Methods: One hundred and fifty-five individuals underwent examination and treatment. These included 22 apparently healthy volunteers aged 25 to 34 years (group 1 or control group), 47 patients with NSD-associated OD only aged 24 to 33 years (group 2 or archival group), 44 patients with NSD-associated OD only aged 23 to 35 years (group 3), and 42 patients with NSD-associated OD and a history of COVID-19 aged 23 to 36 years (group 4). Ten of the patients of group 4 had nasolacrimal duct obstruction. Results: Our magnetic resonance imaging (MRI) studies found that olfactory bulb volume was 27.2% and 54.5% decreased in groups 3 and 4, respectively, compared to healthy volunteers. A procedure for obtaining at least 24 ml of APMC was described. A 4–mm diameter endoscope (Karl Storz, Germany) was used to perform septoplasty under general endotracheal anesthesia in groups 2, 3 and 4. Application of APMC after endoscopic septoplasty in patients presenting with NSD-associated OD, a history of COVID-19 contributed to the normalization of olfactory bulb volume, reduction in postoperative complication rate, and restoration of the sense of smell and quality of life. Application of APMC after endoscopic septoplasty in patients presenting with NSD-associated OD, a history of COVID-19 and nasolacrimal duct obstruction, contributed to restoration of nasolacrimal duct patency, thus preventing chronic dacryocystitis.